2006
DOI: 10.1063/1.2264092
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum ion emission from solid electrolytes: An alternative source for focused ion beams

Abstract: A bright ion source based on the solid electrolyte (AgI)0.5(AgPO3)0.5 has been developed. The solid electrolyte source provides stable currents of Ag+ in the microampere regime that make it suitable for focused ion beam applications. Similar conditions are expected for different solid electrolyte materials and their corresponding ions. This opens a broad field of applications in structuring and modifying devices on a nanometer scale using focused ion beams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The field emission of conducting ions from a solid electrolyte by applying a high voltage has been studied so far, and the emission of O ¹ ions from partially stabilized zirconia, 44) and the emission of Ag + ions from silver phosphate, a silver ion conductor, 45) have been reported. After Hosono reported that electrons were encapsulated in the cage-like 12CaO7Al 2 O 3 (C12A7) crystal and that the electrons could be replaced by other anion species, O ¹ , H ¹ , and F ¹ ion emissions from C12A7 were also reported one after another.…”
Section: Ion Emission From Tip Of Glassesmentioning
confidence: 99%
“…The field emission of conducting ions from a solid electrolyte by applying a high voltage has been studied so far, and the emission of O ¹ ions from partially stabilized zirconia, 44) and the emission of Ag + ions from silver phosphate, a silver ion conductor, 45) have been reported. After Hosono reported that electrons were encapsulated in the cage-like 12CaO7Al 2 O 3 (C12A7) crystal and that the electrons could be replaced by other anion species, O ¹ , H ¹ , and F ¹ ion emissions from C12A7 were also reported one after another.…”
Section: Ion Emission From Tip Of Glassesmentioning
confidence: 99%
“…Typical examples of the useful solid electrolyte materials are yttria-stabilized zirconia (YSZ) as oxide ion conductors, [17] tin-doped PbF 2 representing fluoride ion conductors, [18] and KAg 4 I 4 CN, [19] (AgI) 0.5 (AgPO 3 ) 0.5 , [20] RbAg 4 I 5 , [21,22] CsAg 4 Br 3−x I 2+x , [23,24] Rb 4 Cu 16 I 7 Cl 13 , etc. [25] as silver or copper ion conductors, successfully improving ion conductivity at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, continuous silver ions emissions from an Ag + ion source based on (AgI) 0.5 -(AgPO 3 ) 0.5 SSE was reported by Escher et al in 2006. [20] RbAg 4 I 5 was prepared and investigated in the mid-1960s. [18] In 1967, Owens et al revealed that crystalline compound RbAg 4 I 5 exhibited superior ion conductivity of more than 10 1 S/m at 25 • C with negligible electronic contribution of < 10 −9 S/cm.…”
Section: Introductionmentioning
confidence: 99%